Post-hoc Analysis of Pharmacodynamics and Single-Agent Activity of CD3xCD123 Bispecific Antibody APVO436 in Relapsed/Refractory AML and MDS Resistant to HMA or Venetoclax Plus HMA - Watts, Justin; Lin, Tara L.; Mims, Alice; Patel, Prapti; Lee, Cynthia; Shahidzadeh, Anoush; Shami, Paul; Cull, Elizabeth; Cogle, Christopher R.; Wang, Eunice; Uckun, Fatih M. (Frontiers in Oncology, 2022)
APVO436 is a recombinant bispecific antibody designed to direct host cytotoxic T-cells to CD123-expressing blast cells in patients with hematologic malignancies. APVO436 showed promising tolerability and single-agent activity in relapsed or refractory (R/R) acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS). The primary purpose of this post-hoc analysis was to evaluate the therapeutic and pharmacodynamic effects of APVO436 in 14 R/R AML/MDS patients who had failed treatment with hypomethylating agents (HMA) or venetoclax plus HMA prior to being enrolled in the APVO436 Phase 1 dose-escalation study that was recently completed. Eight of these 14 patients had R/R AML and had failed treatment with HMA (N=2) or venetoclax plus HMA (N=6). The remaining 6 patients had R/R MDS and had also failed treatment with HMA (N=5) or venetoclax plus HMA (N=1). They were treated with APVO436 at submicrogram dose levels >0.08 mcg/kg that were active in preclinical NOD/SCID mouse xenograft models of AML. APVO436 activated patients’ T-cells as evidenced by reduced numbers of circulating CD123+CD34+ and CD33+CD34+ peripheral blasts. Single-agent activity was observed at dose levels ranging from 0.1 mcg/kg to 0.7 mcg/kg in 4 R/R AML patients (50%), including 3 patients with prolonged stable disease (SD) and one patient with complete remission (CR). Likewise, 3 MDS patients had SD (50%) and 3 additional MDS patients (50%) had a marrow CR at dose levels ranging from 0.1 mcg/kg to 0.8 mcg/kg. The median survival for the combined group of 14 R/R AML/MDS patients was 282 days. This early evidence of single-agent activity of APVO436 in R/R AML/MDS patients who failed HMA with or without venetoclax provides proof of concept supporting its in vivo immunomodulatory and anti-leukemic activity and warrants further investigation of its clinical impact potential.